(untitled) (Nuntius Antiquus, 2010)
This paper aims at presenting a reflection on a manuscript of autobiographical nature left by Abel/Adelaide Herculine Barbin, someone with a hermaphroditic condition who was born in 1838 and committed suicide at the age of thirty. Following the trail of Barbin’s text, we will consider its influence as an autobiographical document in which literary and mythical representations are present and preserved. This undertaking is an attempt to conduct a dialogue between myths and text (Barbin’s manuscript).